Types of organizational innovativeness and success in Austrian hotels. Issue 7 (12th October 2015) - Kessler, Alexander; Pachucki, Christoph; Stummer, Katharina; Mair, Michael; Binder, Petra
Abstract : Purpose: – The purpose of this paper is to identify different types of organizational innovativeness in Austrian hotels and analyze their connection to (innovation) success. In the face of growing international competition, innovation is becoming increasingly important for Austria's hotel industry. A prerequisite for innovation is organizational innovativeness. Design/methodology/approach: – This paper is based on a quantitative survey of 255 Austrian hotel businesses with a minimum of five employees. Innovativeness was measured by three dimensions (willingness, ability and possibility to innovate) and success by five dimensions (overall performance: financial, market and employee-related success; innovation success: product and process innovations). Findings were obtained by combining an exploratory factor analysis with a cluster analysis. Findings: – Factor analysis reveals five factors determining organizational innovativeness: "cooperation as trigger for change"; "acceptance of change"; "resource based scope for change"; "pluralism as trigger for change"; and "loose coupling and error-tolerance". The cluster analysis identifies four types of hotels regarding organizational innovativeness indicating differences regarding the success dimensions: "potential innovators hindered by scarce resources and unsupportive structures", "well-resourced conservatives", "potential innovators hindered by a haphazard approach" and "cautious idea hunters". On the whole, results show that a balanced configuration of organizational innovativeness combined with a cautious approach is connected with greater (innovation) success. Research limitations/implications: – Key-informant and survivor biases have to be considered as all items in the questionnaire were evaluated by self-assessment of the hotel management and only successful hotels (in the sense of survival) were analyzed. One important implication is that (innovation) success depends on the system that enables it; therefore, organizational innovativeness is a precondition of successful innovations. Nevertheless, there is little research on organizational innovativeness in the service sector so far. Practical implications: – This paper supports tourism businesses in understanding the concept of organizational innovativeness and its relation to (innovation) success. SMEs, which dominate the Austrian hotel industry, tend to focus on the financial aspect of innovativeness and, in general, do not consider the range of factors that constitute an organization's innovativeness (willingness, ability and possibility to innovate) and the various outcomes. Originality/value: – By combining organizational innovativeness and (innovation) success, the paper applies an important element of innovation theory to the Austrian hotel industry. The characterization of different types of hotels regarding organizational innovativeness and success enables a (self-) assessment for hotel businesses and the deduction of customized implications.